Life of RISC: Formation, action, and degradation of RNA-induced silencing complex - Iwakawa, Hiro-Oki; Tomari, Yukihide (Molecular cell, 2022)
Small RNAs regulate a wide variety of biological processes by repressing the expression of target genes at the transcriptional and post-transcriptional levels. To achieve these functions, small RNAs form RNA-induced silencing complex (RISC) together with a member of the Argonaute (AGO) protein family. RISC is directed by its bound small RNA to target complementary RNAs and represses their expression through mRNA cleavage, degradation, and/or translational repression. Many different factors fine-tune RISC activity and stability-from guide-target RNA complementarity to the recruitment of other protein partners to post-translational modifications of RISC itself. Here, we review recent progress in understanding RISC formation, action, and degradation, and discuss new, intriguing questions in the field.